2017
DOI: 10.1016/j.semcdb.2017.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and cytoskeletal regulations in epidermal development

Abstract: At the surface of the body, the epidermis covers great depth in its developmental regulation. While many genes have been shown to be important for skin development through their associations with disease phenotypes in mice and human, it is in the past decade that the intricate interplay between various molecules become gradually revealed through sophisticated genetic models and imaging analyses. In particular, there is increasing evidence suggesting that cytoskeleton-associated proteins, including adhesion pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 99 publications
(103 reference statements)
0
10
0
Order By: Relevance
“…A keratinized stratified squamous epithelium is composed of cells called keratinocytes. These cells undergo a process of epidermal differentiation or keratinization from the basal layer to differentiating spinous, granular and cornified layers [3]. The keratinocytes in each layer have unique morphological and biochemical features and are under the control of a highly complicated and tightly regulated process.…”
Section: Overview Of Keratinocyte Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…A keratinized stratified squamous epithelium is composed of cells called keratinocytes. These cells undergo a process of epidermal differentiation or keratinization from the basal layer to differentiating spinous, granular and cornified layers [3]. The keratinocytes in each layer have unique morphological and biochemical features and are under the control of a highly complicated and tightly regulated process.…”
Section: Overview Of Keratinocyte Biologymentioning
confidence: 99%
“…The keratinocytes in each layer have unique morphological and biochemical features and are under the control of a highly complicated and tightly regulated process. Several transcription factors, including transcription factors p63, AP‐2γ, Notch and the Wnt signaling pathways, play key roles in controlling keratinization via influencing the proliferation, differentiation and survival of keratinocytes [3]. In addition, signaling through the epidermal growth factor receptor family has been implicated in regulating multiple fundamental processes responsible for the epidermal homeostasis [4,5].…”
Section: Overview Of Keratinocyte Biologymentioning
confidence: 99%
“…Using the scRNAseq atlas, we identified differences in the composition of the suprabasal compartment of HPV+ epithelium. Namely, we found that HIDDEN cells typically form the surface layers of HPV16-infected rafts and are marked by the expression of a broad array of genes implicated in stemness (e.g., KRT15 61 , 62 and KLF5 41 ), terminal differentiation (e.g., TJP3 63 ), and carcinogenesis (e.g., CEACAM6 ) 64 66 . These findings extended to primary human models of the cervical epithelium (+/-HPV18) and tonsillar epithelium (±HPV16), indicating the importance of HIDDEN cells in high-risk HPV-driven diseases at multiple epithelial subsites.…”
Section: Discussionmentioning
confidence: 91%
“…The present study explored the mitigating effect of CDE on the symptoms and pathogenesis of AD by modulating T cells and keratinocytes. As a barrier against external environmental stimuli, the keratin of the skin contributes to ILC2 and Th2 cell activation and hypersensitivity reaction and, eventually, along with the activation of T cells, it induces the characteristics of AD [ 22 ]. Additionally, the immune response regulation through keratin protection from such damage to the skin barrier is reported as a new therapeutic strategy for AD [ 23 ].…”
Section: Discussionmentioning
confidence: 99%